Presupposition, perceptional relativity and translation theory - El-Gamal, Ayman (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2001)
The intertwining of assertions and presuppositions in utterances affects the way a text is perceived in the source language (SL) and the target language (TL). Presuppositions can be thought of as shared assumptions that form the background of the asserted meaning. To translate presuppositions as assertions, or vice versa, can distort the thematic meaning of the SL text and produce a text with a different information structure. Since a good translation is not simply concerned with transferring the propositional content of the SL text, but also its other semantic and pragmatic components, including thematic meaning, a special attention should be accorded to the translation of presupposition. This article examines the intrinsic relation between presupposition and thematic meaning, why the concept is relevant to translation theory, and how presupposition can affect the structure and understanding of discourse. Unshared presuppositions are major obstacles in translation, as cultural concepts may be conveyed through expressions that yield presuppositions. To attain an optimal proximity to the SL text, presupposition needs to be singled out as a distinct aspect of meaning, and distinctions need to be made between definite and indefinite meaning, topic and comment, topic and focus, presupposition and entailment, and presupposition and implicature.